2016
DOI: 10.2147/ijwh.s99970
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after bariatric surgery: improving outcomes for mother and child

Abstract: The significant increase in the prevalence of obesity has led to an increase in the number of obese women who become pregnant. In this setting, in recent years, there has been an exponential rise in the number of bariatric procedures, with approximately half of them performed in women of childbearing age, and a remarkable surge in the number of women who become pregnant after having undergone bariatric surgery (BS). These procedures entail the risk of nutritional deficiencies, and nutrition is a crucial aspect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 71 publications
(134 reference statements)
0
33
0
4
Order By: Relevance
“…A review of the current evidence 193 concluded that there is a better overall obstetric outcome after bariatric surgery compared with women with class III obesity who are managed conservatively. A reduction in the prevalence of gestational diabetes mellitus, pregnancy-associated hypertensive disorders, macrosomia and congenital defects were observed.…”
Section: Evidence Level 2++mentioning
confidence: 99%
“…A review of the current evidence 193 concluded that there is a better overall obstetric outcome after bariatric surgery compared with women with class III obesity who are managed conservatively. A reduction in the prevalence of gestational diabetes mellitus, pregnancy-associated hypertensive disorders, macrosomia and congenital defects were observed.…”
Section: Evidence Level 2++mentioning
confidence: 99%
“…In a recent Danish study, the average weight loss in premenopausal women during the first postoperative year was 39.6 kg (102). Pregnancy should be avoided within 2 years after bariatric surgery and young fertile women should use safe birth control (103). Performing OGTT after bariatric surgery can trigger dumping syndromes and is generally not recommended (104).…”
Section: Bariatric Surgery Gdm and Ogttmentioning
confidence: 99%
“…In general, bariatric procedures should not be regarded as a contraindication to deliver naturally [ 19 , 28 ]. Nevertheless, increased rates of C-section in operated women are reported with some recent publications showing no differences [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…In general, bariatric procedures should not be regarded as a contraindication to deliver naturally [ 19 , 28 ]. Nevertheless, increased rates of C-section in operated women are reported with some recent publications showing no differences [ 28 ]. However, huge variations in C-section rates were found in the literature ranging from about 18 to 60% section rate in operated women compared with 14–29% in control groups [ 28 ].…”
Section: Resultsmentioning
confidence: 99%